The tyrosine phosphorylated carboxyterminus of the EGF receptor is a binding site for GAP and PLC-gamma. - Margolis, B (1990)
Phospholipase C-gamma (PLC-gamma) and GTPase activating protein (GAP) are substrates of EGF, PDGF and other growth factor receptors. Since either PLC-gamma or GAP also bind to the activated receptors it was suggested that their SH2 domains are mediating this association. We attempted to delineate the specific region of the EGF receptor that is responsible for the binding, utilizing EGF receptor mutants, PLC-gamma, and a bacterially expressed TRP E fusion protein containing the SH2 domains of GAP. As previously shown, tyrosine autophosphorylation of the wild-type receptor wsa crucial in mediating the association and in agreement, a kinase negative EGF receptor could bind PLC-gamma or TRP E GAP SH2, but only when cross tyrosine phosphorylated by an active EGF receptor kinase. The importance of autophosphorylation for association was confirmed by demonstrating that a carboxy-terminal deletion of the EGFR missing four autophosphorylation sites bound these proteins poorly. To study the role of EGF receptor autophosphorylation further, a 203 amino acid EGF receptor fragment was generated with cyanogen bromide that contained all known tyrosine autophosphorylation sites. This fragment bound both TRP E GAP SH2 and PLC-gamma but only when tyrosine phosphorylated. This data localizes a major binding site for SH2 domain containing proteins to the carboxy-terminus of the EGF receptor and points to the importance of tyrosine phosphorylation in mediating this association.